2022
DOI: 10.1038/s41420-022-01141-y
|View full text |Cite
|
Sign up to set email alerts
|

Ferrostatin-1 alleviates tissue and cell damage in diabetic retinopathy by improving the antioxidant capacity of the Xc--GPX4 system

Abstract: Diabetic retinopathy (DR) is a common microvascular complication leading to a high blindness rate among patients with diabetes. Ferroptosis is a type of cell death caused by the accumulation of iron-dependent lipid peroxides. Studies have shown that ferroptosis plays an important role in DR. The rat model of DR was constructed and treated with Ferrostatin-1 (Ferr-1). Haematoxylin and eosin (HE) were used to detect the degree of retinopathy. Oxidative stress levels were detected by ELISA. Perl’s staining was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…However, the underlying mechanisms are still unclear. Ferroptosis has been reported to contribute to DR [21]. In the present study, we examined ferroptosis in STZ-induced DR and con rmed that MSC-sEVs could protect vascular endothelial function and maintain BRB stability.…”
Section: Discussionsupporting
confidence: 52%
“…However, the underlying mechanisms are still unclear. Ferroptosis has been reported to contribute to DR [21]. In the present study, we examined ferroptosis in STZ-induced DR and con rmed that MSC-sEVs could protect vascular endothelial function and maintain BRB stability.…”
Section: Discussionsupporting
confidence: 52%
“…Giovanni Miotto et al demonstrated that Fer-1 exerted an inhibitory effect on ferroptosis by scavenging the initial intracellular alkoxy radicals and elevating GSH levels. 42,43 The process of intracellular GSH against ferroptosis required the involvement of the rate-limiting enzyme GPX4. In the ATOtreated NB cells, the transcription of GPX4 was markedly suppressed, leading to a notable reduction in the protein expression level of GPX4.…”
Section: Discussionmentioning
confidence: 99%
“…Giovanni Miotto et al. demonstrated that Fer‐1 exerted an inhibitory effect on ferroptosis by scavenging the initial intracellular alkoxy radicals and elevating GSH levels 42,43 . The process of intracellular GSH against ferroptosis required the involvement of the rate‐limiting enzyme GPX4.…”
Section: Discussionmentioning
confidence: 99%
“…19 It has demonstrated cytoprotective effects against ferroptosis induced by different stimuli, including erastin, RSL3, and HG. 17,20 However, the low potency, poor solubility, and stability impose on the clinic application of Fer-1 which is a great limitation. To overcome these shortcomings, a few improved analogs of Fer-1, such as SRS9-11, SRS9-92, SRS9-86, and UMAC-2148 (Fig.…”
Section: Introductionmentioning
confidence: 99%